Developing Educational Games for Mathematics Learning to Improve Learning Motivation and Outcomes - Claudea Winandyaz Rakasiwi; Muhtadi, Ali (JTP - Jurnal Teknologi Pendidikan, 2021)
This study aims to develop learning educational games as learning media in the mathematics learning process to increase students’ learning motivation and outcomes. Educational games are designed to help students understanding a simple geometric shapes such as angles, sides, and nets. The development model was based on the ADDIE model covering Analyze, Design, Development, Implementation, and Evaluation stages. The result of the feasibility assessment by media and material experts reached 94% and 90% of each. Meanwhile, the assessment by the teacher reached 90%. The result of the initial / pilot test and field test reached 87% and 94% respectively. Based on the assessment, it can be concluded that educational games are suitable for supporting mathematics learning. The increase in students’ learning motivation reached 84.4%, while the learning outcomes increase from 48.9 to 85.1. Further, the gain score reached 0.71 indicating that the educational games are effective for improving learning outcomes.